Evaluating interoperability of ISO 15926 implementation: A case study of IFSWorld Company in the use of data interoperability between computer systems - Pirshahid, Parastoo Ebrahimzadeh (My University, 2013)
Through ongoing global standardization, different specialized organizations are trying to gain stability in the process of plant life-cycle including the stages of design, construction, operation and maintenance. In this regard, exchanging information and knowledge across organizations is of vital importance. ISO 15926 is an international standard for the interoperability and integration of process plant information with other enterprise information. Originally, its information model was established for oil and gas facilities. Implementation of ISO 15926 in organizations depends on available tools supporting the standard. The iRINGTools is a set of open source tools supporting ISO 15926 that is being developed by initiators of the standard. This report evaluates ISO 15926 and its tools with the purpose of identifying gaps between what the standard and tools offer and what users expect from them. In doing so, IFSWorld Operations Company was selected as a case study for this research. IFSWorld is a software company based in Sweden that develops ERP applications for a major group of customers in the oil and gas industry. Results obtained from this study show that the standard and its open-source tools are still under development and need some increments and modifications to meet user expectations. In particular, the ISO 15926 Reference Data Library (RDL) is not complete yet and at the time, iRINGTools does not support the converting of values, class hierarchy and relationship between data. This report provides users with information about what they can expect from the current state of ISO 15926 standard and its tools. Moreover, this information could be useful for suppliers of the standard to know about users' expectations. The intended audiences of the paper are engineers who work with systems integration and collaboration in architecture and engineering of plants for oil and gas facilities.
Keywords: Data- och informationsvetenskap; Computer and Information Science